Hydrolytic enzymes mediated lipid-DNA catabolism and altered gene expression of antioxidants under combined application of lead and simulated acid rain in Fenugreek (Trigonella foenum graecum L.) seedlings - Xalxo, Roseline (Ecotoxicology (London, England), 2018)
Understanding ill effects of simultaneous existence of various abiotic stresses, commonly observed due to various anthropogenic activities and global climate change these days, over plants growth, metabolic activity and yield responses are important for continued agricultural productivity and food security. In the present study, seedlings of Fenugreek (Trigonella foenum graecum L.) were subjected to lead (Pb, 1200 ppm) and/or simulated acid rain (SAR, pH 3.5) for 30 days, and were then analysed. The results revealed reduced growth, and total lipid and DNA contents, while enhanced Pb accumulation, biological concentration factor, biological accumulation coefficient, translocation factor, lipase activity, and levels of free fatty acid, conjugated diene, lipid hydroperoxide, DNA oxidation and DNase activity under Pb and/or SAR exposure. Additionally, activities and gene expression levels of antioxidants (superoxide dismutase, catalase, guaiacol peroxidase and ascorbate peroxidase) were enhanced in response to applied treatments. The results also suggested that inhibitions/ accelerations determined under joint addition of Pb and SAR were comparatively more profound than those measured under their single application. Additionally, root was more sensitive to Pb treatment, compared to both leaf and shoot. Hence, under simultaneous presence of two or more number of abiotic stresses, the strategy opted by plants for survival is chiefly governed by the interaction between prevailing stressors, which is then conceived by plants as a new state of stress